Different Level of Carotid-Femoral Pulse Wave Velocity and Related Factors in Different Nationality Group in China - Liu J; Cui X; Wen H; Bai X; Jiang S; Zhao H; Li L; Wang H (Vascular Health and Risk Management)
Jinbo Liu,1– 3 Xuechen Cui,1 Huan Wen,1 Xiu Bai,1 Shantong Jiang,1 Hongwei Zhao,1 Lihong Li,1 Hongyu Wang1– 5 1Department of Vascular Medicine; Peking University Shougang Hospital, Beijing, People’s Republic of China; 2Beijing Shijingshan District Key Clinical Specialty of Vascular Medicine, Beijing, People’s Republic of China; 3Vascular Health Research Center of Peking University Health Science Center (VHRC-PKUHSC), Beijing, People’s Republic of China; 4Key Laboratory of Molecular Cardiovascular Sciences (Peking University), Ministry of Education, Beijing, People’s Republic of China; 5Heart and Vascular Health Research Center of Peking University Clinical Research Institute (HVHRC-PUCRI), Beijing, People’s Republic of ChinaCorrespondence: Hongyu Wang, Department of Vascular Medicine; Peking University Shougang Hospital, Beijing, People’s Republic of China, Tel +8610-57830226 ; Fax +8610-57830077, Email dr.hongyuwang@foxmail.comBackground: Higher level of carotid-femoral pulse wave velocity (CF-PWV) is indicating higher level of arterial stiffness. China has a population of 1.4 billion, with 1.2 billion population in Han ethnicity, 9.4 million population in Miao ethnicity, 700 thousand population in She ethnicity. We chose these three ethnic groups for analysis, to find some similarities or differences in CF-PWV.Methods: We launched early vascular lesion detection technology promotion involving several regions such as the Han (Beijing), Miao (Guizhou Province), and She (Fujian Province) ethnicity. We conducted population testing in different regions and based on the inclusion and exclusion criteria, 1481 individuals were ultimately included. There were 942 han subjects, 186 Miao subjects and 353 She subjects. The CF-PWV was measured using a Complior device.Results: The CF-PWV was significantly higher in Han population than in Miao and She population. Levels of systolic blood pressure (SBP) and diastolic blood pressure (DBP) were significantly lower in Han ethnicity than in Miao and She ethnicity. The composition of male, smoking, hypertension and diabetes mellitus were significantly higher in Han ethnicity than in Miao and She ethnicity. Multiple linear regression analysis showed that age, body mass index (BMI), diabetes mellitus, creatinine, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), SBP, and ethnicity were independent associated with the CF-PWV in all subjects. And compared with the Han ethnicity, CF-PWV was significantly lower in Miao and She ethnicity (β= − 0.295, β= − 0.241, both p< 0.001).Conclusion: CF-PWV was significantly higher in Han ethnicity than in Miao and She ethnicity. The factors associated with the CF-PWV differed among different ethnicity indicated that different prevention and control strategies needed to be adopted for different ethnic groups and risk factors in different regions to reduce the progression of arteriosclerosis in the local population.Keywords: carotid-femoral pulse wave velocity, Han ethnicity, Miao ethnicity, She ethnicity